Choosing a brand name that's "in" – disgust sensitivity, preference for intuition, and the articulatory in-out effect. (February 2022) - Ingendahl, Moritz; Vogel, Tobias
Abstract: Words with an inward-wandering consonant sequence (e.g., MADIKO) are preferred to words with an outward-wandering consonant sequence (e.g., KADIMO), commonly referred to as articulatory in-out effect. Despite its robustness in consumer behavior across languages and settings, there has been no research on interindividual differences in this effect so far. Based on current theories on the phenomenon, we expect that the in-out effect should be moderated by interindividual differences in disgust sensitivity and preference for intuition. In a preregistered, high-powered study ( N  = 298), we replicate the in-out effect in the domain of brand names. However, neither disgust sensitivity nor preference for intuition has a moderating influence. Our findings suggest that the in-out effect is likely to be observed across levels of these personality traits. We discuss further implications of these findings for the processes underlying the effect.